Toward a Scholarly Edition of Beckett's Critical Writings. Issue 1 (April 2015) - Tucker, David; Nixon, Mark
<x xml:space="preserve">Abstract</x> This essay outlines the case for a new, scholarly edition of Beckett's critical writings, one that would be complete and with critical annotation. For the most part these texts (critical writings, tributes, in memoria and epigraphs) have been published in a range of places. As well as in the magazines, newspapers, books and special-issue publications in which pieces originally appeared, a number were collected in Disjecta (Calder 1983 & Grove 1984). This volume, however, is not exhaustive; it misses out a number of important texts (not least Proust) and contains some textual inaccuracies. Furthermore, Beckett's critical writings are currently not available from the UK publishers Faber and the Grove Press Centenary Edition of Beckett's works, the fourth volume of which contains a section entitled 'Criticism', presents only three works of criticism by Beckett (Proust, 'Dante … Bruno . Vico . . Joyce' and 'Three Dialogues'). In this essay, we give a brief (and far from exhaustive) overview of the publication history of Beckett's non-fiction prose texts, before outlining some of the editorial challenges they pose. Although Beckett tended to be dismissive of these works, they form an integral part of his canon.